Rare Presentation of HAV infection in 7 year old child (Journal of Dhaka National Medical College & Hospital, 2016)
Hepatitis A (HAV) infection is one of the most common forms of hepatitis in the pediatric age group in developing countries. It is usually self limiting and rarely accompanied by extrahepatic complication. In this article, we report one child with hepatitis A who had associated pleural effusion, ascites and acalculus cholecystitis. The child improved with resolution of hepatitis after symptomatic treatment. Although uncommon extra hepatic manifestations can occur with hepatitis. However this child resolve completely. Paediatricians in developing countries should be aware of this rare association to avoid unnecessary investigationsJ. Dhaka National Med. Coll. Hos. 2016; 22 (01): 50-52